THE QURAN AND PSYCHOLOGICAL STRESS IN THE ELDERLY DURING THE COVID-19 PANDEMIC - Ardhian Darmawan; Niken Setyningrum; Anisa Saputri (International Islamic Medicine Forum, 2022)
The COVID-19 pandemic has had a significant global health impact. This condition requires the government to make self-quarantine rules. The imposition of activity restrictions that last a long time has an impact on physical and psychological conditions, especially in the elderly. The perspective of the mind experienced by the elderly due to seeing and feeling the conditions that occur is at risk of giving psychological pressure to the elderly. The Qur'an which contains a strand of wisdom is expected to make a positive contribution to the psychology of the elderly due to the impact of COVID-19. Research with quantitative type and the number of samples as many as 126 elderly. Analysis of the data used using the Kendall's tau test. The results of this study indicate that there is a relationship between the intensity of reading the Qur'an with psychological stress in the elderly with a P value of 0.000 (p <0.05). The high intensity of reading the Qur'an contributes to the onset of psychological stress in the low and moderate ranges. Reading the Qur'an can be used as therapy for the elderly who have mental disorders and this therapy is able to bring meaning to the lives of the elderly